From marine neglected substrata new fungal taxa of potential biotechnological interest: the case of Pelagia noctiluca - Pasqualetti, Marcella; Braconcini, Martina; Barghini, Paolo; Gorrasi, Susanna; Schillaci, Domenico; Ferraro, Donatella; Della Sala, Gerardo; De Marino, Simona; Fenice, Massimiliano (Frontiers in Microbiology, 2024)
Introduction - The marine environment is extremely complex and exerts strong evolutionary pressure often leading to the appearance of microbial strains with new metabolic competencies. Microorganisms in marine ecosystems are still largely unknown and should be explored and conserved for biodiversity preservation, possible ecosystem restoring, and other applications. Biodiversity conservation should become a basic ecological strategy of particular significance in relation to global change. In this context, the present research aimed at exploring the culturable mycobiota associated with the jellyfish Pelagia noctiluca, never studied before. In addition, the isolated strains were tested for potential application (antimicrobial activity and presence of genes related to the production of secondary metabolites). Methods: Five jellyfishes were collected in the coastal area of Giglio Island and processed to isolate epizoic fungi. The strains were identified using a polyphasic approach (morphological, physiological and molecular) and their salt preference was also investigated. The antifungal and antibacterial activity were tested for each strain with agar plug diffusion test. The presence of some key genes related to the main pathways for the production of secondary metabolites in fungi, polyketide synthases (PKSs), and non-ribosomal peptide synthetases (NRPSs), was also assessed. Results: A total of 164 isolates were obtained; after the dereplication, 40 morphotypes, and 23 species were identified. The phylogenetic analyses suggested the presence of new taxa belonging to Pleosporales: two new genera and species, and a new species of Tamaricicola. The detected mycobiota showed a relatively high diversity, if compared to other epizoic fungal communities. All isolated strains were marine fungi as confirmed by their salt preference and marked euryhalinism. The genes related to the two main pathways for the production of secondary metabolites in fungi, PKSs and NRPSs, were identified in 4 and 9 strains, respectively. The antimicrobial activity was revealed in 70% of the strains, including the new taxa. The abundance of bioactive strains may be related to the potential involvement of epizoic fungi in host defence strategies. Moreover, these strains could show a high potential for further biotechnological applications particularly in the case of new taxa. All strains are maintained in culture collections.